BEYOND MODERNITY: NIETZSCHE AND THE FRANKFURT SCHOOL - das Chagas Lacerda, Oclécio (Seven Editora, 2025)
The aim is to develop a philosophical analysis capable of proposing alternatives to the problems of modernity diagnosed by Nietzsche and the Frankfurt philosophers Adorno and Benjamin. According to these philosophers' critical analysis of the modern world, human life follows a path of decadence and poverty. A deviation from this path is proposed, in search of a higher conception of life, in which there is a just balance between spiritual and material conditions. This deviation must occur through the intensification of the state of decadence and poverty, proliferated in all components of the prevailing culture.DOI: https://doi.org/10.56238/sevened2025.029-063